Fabry-perot interferometers with resin scaffolders for high sensitivity temperature sensing - Zeng, Yu; Zhang, Pengyu; Li, Zhiqi; Shen, Jian; Li, Chaoyang (Frontiers in Physics, 2024)
This study explores the development of an innovative Fabry-Perot Interferometer (FPI) designed for temperature sensing and environmental monitoring. The device is constructed by embedding optical fibers within a 3D-printed resin scaffold, forming a structure with an open Fabry-Perot cavity. Intended as an integral component of Cyber-Physical-Social Systems (CPSS), this FPI structure aims to enhance the system's capacity to sense changes in external environmental conditions. Within the CPSS context, the FPI offers several advantages, including simple manufacturing processes, low production costs, and high sensitivity. These benefits contribute to providing precise environmental feedback to the system, which is essential in implementing effective security and privacy protection strategies. Experimental evaluations have shown that the FPI exhibits a high linear sensitivity of 14.330 nm/°C within a temperature range of 34.9°C to 38.5°C, confirming its potential for application in CPSS for temperature monitoring and environmental sensing.